The Kant-Maimonides Constellation - Wiedebach, Hartwig (The journal of Jewish thought & philosophy, 2012)
Responding to Zachary Braiterman’s and Daniel Garner’s ideas on post-Holocaust religious thought, the author proposes a new model of relationships between theodicy and antitheodicy in which divine perfection is no longer privileged as the single key factor. Building on Peter Berger’s and Clifford Geertz’s treatments of the problem of evil, it is suggested that focusing on meaning-making and tradition can result in a stratified view of theodicy–antitheodicy more able to engage with the dynamics of several well-known thinkers associated with religious responses to the Holocaust.